STUDY OF THE INFLUENCE OF BIOREGULATORS ON THE PRODUCTIVITY AND DEVELOPMENT OF PLANTS GROWN BY HYDROPONICS - Nurlybek Abdimutalip; Zhuldyz Tulpan; Klara Gul (Scientific Journal of Pedagogy and Economics, 2021)
In many regions of the Republic of Kazakhstan, the environmental situation is deteriorating. The total area of the territory of the Republic of Kazakhstan according to the land balance as of November 1, 2013 is 272.5 million hectares. In recent years, under the influence of natural and anthropogenic factors, the volume of pastures has increased per unit area, soil fertility has decreased, irrigation and rainwater nutrients have decreased, salinization and irrigation areas have decreased, crop yields have decreased, and water and soil pollution are increasing, and certain species of flora and fauna are at risk of extinction. Most of the Republic’s territory is located in desert zones (60% of the territory). In agriculture, industry and everyday life, the role of hydroponics is increasing. One of the reasons for this is a reduction in the financial costs of tillage, protection from weeds and pests when using the hydroponics method, as well as an increase in a large number of plants on a limited landing site. Water and mineral fertilizers are spent more efficiently due to their repeated use. Growing plants using hydroponics is very profitable, since in a short period of time you can get a crop using year-round and small areas. Here, an important role is played not only by macro-and know the concentration of trace elements. As a result, plants do not realize their potential, and therefore do not always give a high-quality product. The use of hydroponics also reduces the financial costs of soil cultivation, protection from weeds and pests, and will increase the number of plants on the landing site with a limited volume.